2018
DOI: 10.1088/1361-6455/aaa182
|View full text |Cite
|
Sign up to set email alerts
|

Dielectronic recombination of the open 4d-shell of tungsten: W37+–W28+

Abstract: Tungsten is an important element for magnetically confined fusion plasmas but has the potential to cool, or even quench the plasma due to it being an efficient radiator. Total and level-resolved dielectronic recombination (DR) rate coefficients, for all ionization stages, are essential to model tungsten. We describe a set calculations performed using the distorted wave code autostructure for the tungsten ions W 37+ to W 28+ . We demonstrate the importance of relativistic configuration mixing in such calculatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
(104 reference statements)
0
8
0
Order By: Relevance
“…Our previous study reported the electron-impact MRC only from the ground levels of the ions [24][25][26]. The current results are presented for thirteen temperature values in the range from 1.46•10 6 K to 7.29•10 9 K. It should be noted that peak abundance temperature obtained from the modeling for W 26+ equals 1×10 7 K [27,28]. The study of MRC includes the EA channels corresponding to the excitations to shells with principal quantum numbers n 8 and 9 n 25.…”
Section: Introductionmentioning
confidence: 76%
“…Our previous study reported the electron-impact MRC only from the ground levels of the ions [24][25][26]. The current results are presented for thirteen temperature values in the range from 1.46•10 6 K to 7.29•10 9 K. It should be noted that peak abundance temperature obtained from the modeling for W 26+ equals 1×10 7 K [27,28]. The study of MRC includes the EA channels corresponding to the excitations to shells with principal quantum numbers n 8 and 9 n 25.…”
Section: Introductionmentioning
confidence: 76%
“…Next, we show our results, and compare our rate coefficients to currently available literature. We then calculate an updated steady state ionization fraction including the data calculated in this work, and the data calculated in [11][12][13]. Finally, we conclude the paper, and discuss future work on the open 4f-shell of tungsten.…”
Section: Introductionmentioning
confidence: 94%
“…We now compare two sets of ionization fractions, calculated using recombination rate coefficient data from this work (61-to 73-like) and The Tungsten Project (00-to 46-like, [11,12,13]), and using the scaled data from Pütterich et al [3]. For the ionization fraction calculated using the present data, we use the data from Pütterich et al for 47-to 60-like, as we have not calculated data for these charge states yet.…”
Section: Steady State Ionizationmentioning
confidence: 99%
See 1 more Smart Citation
“…[124] In addition, a systematic theoretical calculations of recombination rate coefficients for tungsten ions have been performed by employing the AU-TOSTRUCTURE code and can be found in the references in Refs. [125][126][127].…”
Section: Applications In the Astrophysical And Fusion Plasmasmentioning
confidence: 99%